The influence of corporate management on economic development and growth - Kryshtal, Halyna (Management and Entrepreneurship: Trends of Development, 2022)
The purpose of the article is to identify the impact of corporate governance on the economic development and growth of the state. The article proposes possible channels for the growth and development of corporate governance: good corporate governance can expand companies' access to external financing, which, in turn, contributes to the attraction of new investments, higher rates of economic growth and the creation of new jobs; good corporate governance can reduce the cost of capital and increase company value, making investment more attractive, leading to further economic growth and increased employment; effective management increases operational efficiency due to better allocation of resources and improvement of management, helps more equal distribution of welfare; effective corporate governance reduces the risk of a financial crisis, which can cause devastating economic and social consequences; effective corporate governance leads to improved relations with all interested parties (stakeholders) and, accordingly, improved labor relations, as well as creating conditions for working on social problems, in particular, issues of environmental protection.The theoretical and methodological basis of the research is represented by the scientific works of leading scientists in the field of corporate governance, as well as the author's interpretation of the impact of corporate governance on the economic development and growth of the state. In the research process, such methods as analysis and synthesis, the method of historical and logical modeling were used. As theoretical methods, the formalization method, the "from abstract to concrete" method, as well as the historical method and the method of economic interpretation are used in the work. From a practical point of view, the method of grouping statistical data, statistical and econometric analysis was also used in the study.JEL Classification: G34; D74.